Speaking in signs: Communicating the gospel with deaf people in Zimbabwe - Kimion Tagwirei (Verbum et Ecclesia, 2021)
Churches in Zimbabwe have excluded deaf people, limiting their access, presence and participation in Missio Dei and Missio Ecclesiae. So far, there is minimal Zimbabwean theological scholarly attention to communicating the gospel with deaf people. Much of the available related literature focusses on education for deaf people. This article applies a critical disability theory, which is explanatory, practical, normative, and promotes equality and inclusion. In this contribution, communication of the gospel with deaf people is explored. Against the backdrop of marginalisation of deaf people and the inconsideration of the hearing Church, this study interrogated the gospel communication gap that needs to be bridged between deaf people and the hearing Church. The culture of deaf people and communication of the gospel in Zimbabwe were examined. Reflecting through a topic ‘Speaking in signs: Communicating the gospel with deaf people in Zimbabwe’, using a qualitative research methodology through interviews with 20 participants from different institutions for deaf people and Evangelical Fellowship of Zimbabwe, this research observed that very few denominations have reached out to deaf people with the gospel, whilst the majority have not. The study challenges traditionally exclusive Zimbabwean ecclesiology, missiology and communication of the gospel. It recommends inclusive and contextualised communication of the gospel through the incorporation of sign language and deaf culture towards effective evangelisation and discipleship of deaf people.